Frequency distribution of mouth breathing in children based on age and gender - Damayanti, Yoswita; Soewondo, Williyanti; Primarti, Risti Saptarini (Padjadjaran Journal of Dentistry, 2014)
Introduction: Mouth breathing is one of the bad habits caused by respiratory tract obstruction, a habit, or the anatomically incompetent lip shape. It causes an abnormality on the customs of dentofacial, academic, health, and children behavior. The purpose of this research is to find out the percentage of children aged 6-12 years old who have a mouth breathing habit in Pedodontics Installation of Dentistry Unpad Bandung, in September-October 2011. Methods: The study was performed using descriptive method. The study subject are 110 children collected by accidental sampling. Research conducted by clinical examination of extra and intra oral as well as a questionnaire through interviews. Results: The results showed that there were 12 children who have a mouth breathing (10.1%), on the basis of age there are 3 children (25%) at the age of 10 years at most have a habit of breathing through the mouth, and on the basis of gender, there are five male children (41.7%) and 7 female children who have a habit of breathing through the mouth (58,3%). Conclusion: Conclusions of this research showed that the frequency distribution of a child with mouth breathing in Pedodontics Instalation of RSGM FKG Unpad is relatively low with the number of incidence in female children higher than male children.